Empowering smart city governance through decentralized blockchain solutions for security and privacy in IoT communications - Zainuddin, Ahmad Anwar; Muhammad, Nurul Fadhilah Ahmad; Hasli, Amir Husaini Mohd; Zaini, Nor Ani Jannah Ahmad; Karimudin, Nureen Batrisyia Balqis; Bahri, Hannah Sabrina Saiful; Nizam, Muhamad Khaleesh Mirza Khairul; Kamarudin, Saidatul Izyanie; Ghazalli, Nasyitah (Association for Scientific Computing Electrical and Engineering, 2023)
This paper highlights the benefits and challenges of smart cities, which leverage technology to offer a wide range of services to citizens. While these services have the potential to greatly improve the quality of life in metropolitan areas, they also raise significant privacy and security concerns. The study emphasizes the need to employ